European Works Councils Experiences - Skorupińska, Katarzyna (Comparative Economic Research. Central and Eastern Europe, 2012)
In September, 2011 there was 15th anniversary of the implementation of the first EU directive creating European Works Councils (EWCs). This is also the year when the new version of the directive was put in force, i.e. Directive 2009/38/EC. EWCs are a form of indirect employee participation on European level which guarantees workers the right to information and consultation. The employees’ representatives of all undertakings of transnational company were given the opportunity to voice their opinion about the decisions to be made by central management of the company. In this article three major topics are discussed: the role of European Works Councils in EU countries, the range of these institutions of employee participation on European level and changes in EWCs’ functioning introduced by the new EWC directive. The main aim of the paper is to present diverse patterns of these institutions as well as to attempt the evaluation of EWCs effectiveness and their influence on the system of industrial relations in Europe.